Donor-derived Cell-free DNA: Advancing a Novel Assay to New Heights in Renal Transplantation. Issue 3 (4th February 2021) - Paul, Rohan S.; Almokayad, Ismail; Collins, Ashte; Raj, Dominic; Jagadeesan, Muralidaran
Abstract : Despite advances in transplant immunosuppression, long-term renal allograft outcomes remain suboptimal because of the occurrence of rejection, recurrent disease, and interstitial fibrosis with tubular atrophy. This is largely due to limitations in our understanding of allogeneic processes coupled with inadequate surveillance strategies. The concept of donor-derived cell-free DNA as a signal of allograft stress has therefore rapidly been adopted as a noninvasive monitoring tool. Refining it for effective clinical use, however, remains an ongoing effort. Furthermore, its potential to unravel new insights in alloimmunity through novel molecular techniques is yet to be realized. This review herein summarizes current knowledge and active endeavors to optimize cell-free DNA-based diagnostic techniques for clinical use in kidney transplantation. In addition, the integration of DNA methylation and microRNA may unveil new epigenetic signatures of allograft health and is also explored in this report. Directing research initiatives toward these aspirations will not only improve diagnostic precision but may foster new paradigms in transplant immunobiology.